Temperature control of microbial respiration and growth efficiency in the mesopelagic zone of the South Atlantic and Indian Oceans - Mazuecos, Ignacio P.; Arístegui, Javier; Vázquez-Domínguez, Evaristo; Ortega-Retuerta, E.; Gasol, Josep M.; Reche, Isabel (Deep Sea Research Part I: Oceanographic Research Papers, 2015)
8 pages, 6 figures, 5 tables We have measured both prokaryotic heterotrophic production (PHP) and respiration (R), then providing direct estimates of prokaryotic growth efficiencies (PGE), in the upper mesopelagic zone (300-600m) of the South Atlantic and Indian Oceans. Our results show that in situ R ranged 3-fold, from 87 to 238μmolCm-3d-1. In situ PHP rates were much lower but also more variable than R (ranging from 0.3 to 9.1μmolCm-3d-1). The derived in situ PGE values were on average ~1.4% (from 0.3% to 3.7%), indicating that most of the organic substrates incorporated by prokaryotes were respired instead of being used for growth. Together with the few previous studies on PGE published before for the Atlantic Ocean and Mediterranean Sea, our findings support the hypothesis that the global mesopelagic zone represents a key remineralization site for export production in the open ocean. We also found a strong correlation between R and PGE with temperature across a gradient ranging from 8.7 to 14.9°C. The derived Q10 value of 3.7 suggests that temperature variability in the mesopelagic zone plays a significant role in the remineralization of organic matter. © 2014 Elsevier Ltd. This paper is a contribution to the INGENIO 2010 CONSOLIDER program (CDS2008-00077). IPM was supported by a JAE Pre-doc fellowship, from the Spanish National Research Council (CSIC) and the BBVA Foundation, Spain. IPM, JA and JMG were partly supported by Project HotMix (CTM2011-30010-C02/MAR) Peer Reviewed